2017
DOI: 10.5897/jat2017.0271
|View full text |Cite
|
Sign up to set email alerts
|

Mergers, taxation and accounting performance: Some evidence from Greece

Abstract: The study examines the merger effects on the accounting performance of Greek firms, in parallel with their taxation impact, during the period of economic crisis in Greece. The study analyses twelve accounting measures from financial statements and financial ratios of a sample of Greek listed firms in the Athens Exchange that carried out one merger in the period from 2010 to 2015 as acquirers. The results revealed that none of the twelve examined accounting measures have changed significantly due to the merger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(94 reference statements)
2
5
0
Order By: Relevance
“…Similar conclusions have been drawn earlier studies based on stock market or accounting performance measures that supported no significant results after mergers per industry [13,16]. On the other hand, different conclusions that there is (a) an improvement at performance in different industry than technology-intensive industrial sector were found by Pazarskis et al [1], or (b) an improvement at performance of the technology-intensive industrial sector were found by Alexandrakis et al [22].…”
Section: Intra-industry Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Similar conclusions have been drawn earlier studies based on stock market or accounting performance measures that supported no significant results after mergers per industry [13,16]. On the other hand, different conclusions that there is (a) an improvement at performance in different industry than technology-intensive industrial sector were found by Pazarskis et al [1], or (b) an improvement at performance of the technology-intensive industrial sector were found by Alexandrakis et al [22].…”
Section: Intra-industry Resultssupporting
confidence: 87%
“…There is no significant change of the examined number of the quantitative variables. Similar conclusions with no significant results after mergers per industry have been drawn earlier studies examining several accounting performance measures for the commercial and services sector after mergers [1,13]. Finally, some other researchers concluded that there is a worsening in performance [16,22].…”
Section: Intra-industry Resultssupporting
confidence: 81%
See 3 more Smart Citations